2008
DOI: 10.1111/j.1744-313x.2007.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine IL12A and IL12B gene mapping, variation and evidence of association with lytic complement and blood leucocyte proliferation traits

Abstract: Interleukin-12, a heterodimeric cytokine consisting of glycosylated subunits of 35 and 40 kDa, is a central molecule in controlling innate as well as adaptive immunity. This study was aimed to investigate the role of IL12A and IL12B as candidate genes for immune competence in pigs. The porcine genes were screened for polymorphism and association analysis was carried out by mixed model analysis with parameters of innate immunity, in vitro haemolytic complement activity in the classical and alternative pathways,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is a heterodimeric proinflammatory cytokine formed by a 35‐kDa chain (encoded by the IL‐12A gene) and a 40‐kDa chain (encoded by the IL‐12B gene) . The p40 subunit (IL‐12B) may also form homodimers, which can bind to IL‐12 receptors and inhibit the activation induced by the IL‐12 heterodimer as well as modulate IL‐12 function . In patients with RA, initial studies have identified IL‐12 residing in the synovial cells of inflamed joints .…”
Section: Introductionmentioning
confidence: 99%
“…It is a heterodimeric proinflammatory cytokine formed by a 35‐kDa chain (encoded by the IL‐12A gene) and a 40‐kDa chain (encoded by the IL‐12B gene) . The p40 subunit (IL‐12B) may also form homodimers, which can bind to IL‐12 receptors and inhibit the activation induced by the IL‐12 heterodimer as well as modulate IL‐12 function . In patients with RA, initial studies have identified IL‐12 residing in the synovial cells of inflamed joints .…”
Section: Introductionmentioning
confidence: 99%
“…To most infectious diseases, the resistance of an individual is resulted from both innate immunity and acquired immunity. The capacity of innate immunity or acquired immunity is more or less controlled by genes [1-4]. The resistance to some diseases is due to a single gene [5,6], but for most diseases it is due to multiple genes [7], among which a few genes (QTL or major genes) have relative large effects and thus play important role in disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…To these infectious diseases, the resistance of an individual resulted from both innate and acquired immunity. The capacity of innate immunity or acquired immunity is more or less controlled by genes [2325]. In pigs, genetic studies have revealed several genes that participate in the resistance to diseases [26] including single-gene porcine ryanodine receptor (ryr1) regulating malignant hyperthermia [27] and porcine factor H [28].…”
Section: Introductionmentioning
confidence: 99%